2022
DOI: 10.3390/w14030506
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Shallow Freshwater Lakes Hydrology in the Yangtze Floodplain from Stable Water Isotope Tracers

Abstract: Stable isotopes of lake waters are widely used to identify the relative importance of hydrological processes on the lake water balance across the ungauged landscape via the coupled-isotope tracer model. The isotopic compositions of twenty shallow freshwater lakes across the mid-lower reaches of Yangtze floodplain (MLY) were investigated in January and May of 2018. The lake-specific input water (δI) and evaporation-to-inflow (E/I) ratios were estimated to explore the specific lake hydrology across the MLY. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The significant negative correlation between DIC concentration and δ 18 O only occurred downstream of Dongting and Poyang lake; thus, the flow of lakes mixed into main stream enriches hydrological signals and contributes to the dilution effect of DIC (Figure 10a). Wide surface area and slow runoff make water in lakes suffer intense sub‐cloud secondary evaporation, thus more enriched deuterium and oxygen signal formed in lakes than that in main stream (Deng et al., 2016; Ding et al., 2014; Li, Song, et al., 2022). Isotopic source analysis (δD and δ 18 O) showed that the contribution of Dongting Lake and Poyang Lake to the main stream discharge in December was 26.7% and 16.5%, compared with 55.7% and 33.1% in May.…”
Section: Discussionmentioning
confidence: 99%
“…The significant negative correlation between DIC concentration and δ 18 O only occurred downstream of Dongting and Poyang lake; thus, the flow of lakes mixed into main stream enriches hydrological signals and contributes to the dilution effect of DIC (Figure 10a). Wide surface area and slow runoff make water in lakes suffer intense sub‐cloud secondary evaporation, thus more enriched deuterium and oxygen signal formed in lakes than that in main stream (Deng et al., 2016; Ding et al., 2014; Li, Song, et al., 2022). Isotopic source analysis (δD and δ 18 O) showed that the contribution of Dongting Lake and Poyang Lake to the main stream discharge in December was 26.7% and 16.5%, compared with 55.7% and 33.1% in May.…”
Section: Discussionmentioning
confidence: 99%